Diagnóstico tardío de aspiración de un cuerpo extraño en la vía aérea, reporte de caso en un adolescente - Rodríguez-Hidalgo, Luis A. (2025)
Aspiration of a foreign body into the tracheobronchial tree is a common event. Although coughing is the most frequent symptom, there are asymptomatic cases that delay diagnosis. Additionally, this condition may experience further diagnostic delay in adolescents, as they might withhold pertinent information. We report the case of a 16-year-old male patient who presented with dry cough, low-grade fever, malaise, and dyspnea. On examination, tactile fremitus, decreased vesicular breath sounds, dullness to percussion, and crackles were identified in the lower two-thirds of the right hemithorax. Chest computed tomography revealed consolidation in the right middle and lower lobes. Video bronchoscopy was performed, and a conical plastic foreign body was extracted. In such cases, patient history is crucial. Our young patient underestimated the choking event, which led to a delayed diagnosis and subsequent complications.